2010
DOI: 10.1016/j.ejso.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological study on the safety of the endoscope-assisted microsurgical removal of vestibular schwannomas

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ARTICLE IN PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Drilling of the IAC was performed with aid of CT based navigation images and the lateral portion of the IAC was opened with endoscope. It was observed that the use of endoscopy and navigation through RSA approach maximized the exposure of the IAC-fundus without injury to the labyrinth 21,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drilling of the IAC was performed with aid of CT based navigation images and the lateral portion of the IAC was opened with endoscope. It was observed that the use of endoscopy and navigation through RSA approach maximized the exposure of the IAC-fundus without injury to the labyrinth 21,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the use of endoscopy and navigation in VS surgery through the RSA to preserve labyrinth integrity 21,30 . Drilling of the IAC was performed with aid of CT based navigation images and the lateral portion of the IAC was opened with endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly endoscopes are used for visualization of the drilled-out portion of the petrous bone for opened air cells that might need sealing. Some authors report that the risk of cerebrospinal fluid leaks have been lowered or even completely avoided (Valtonen et al 1997, Wackym et al 2002, Gerganov et al 2010. Under specific anatomical conditions angled endoscopes can be beneficial to identify and manage high jugular bulb (Betka et al 2010).…”
Section: Rationale For Endoscopic Surgery Of the Vestibular Schwannomamentioning
confidence: 99%
“…Thus it is mandatory to achieve synchronized, in-and-out movements of the endoscope together with the instruments (Jarrahy et al 2002a, Jarrahy et al 2002b, Kabil & Shahinian, 2006, de Vitiis et al 2007). Using the video-endoscopy assisted microsurgical technique the handling of instruments is controlled by the microscope befor e comin g in fr on t of t h e len s of t h e endoscope , Miyazaki et al 2005, Betka et al 2010, Gerganov et al 2010. Another potential risk of the endoscopic technique is possibility of heat injury from prolonged use of the endoscope too close to the cranial nerves and other brain structures (Betka et al 2010, Gerganov et al 2010).…”
Section: Rationale For Endoscopic Surgery Of the Vestibular Schwannomamentioning
confidence: 99%
See 1 more Smart Citation